Hepatitis por citomegalovirus: Presentación de dos casos - Tori, Carlos (2013)
Two cases of hepatitis by cytomegalovirus are described, one in a child and the other in a young adult, presenting with a history of fever, general malaise, hepatomegaly and no jaundice. Their blood test showed atypical lymphocytes, normal bilirubin, elevated liver enzymes, and IgG antibodies against cytomegalovirus. Their course was un was unremarkable except for asthenia which persisted in spite of clinical and laboratory improvement. This course was unremarkable except for asthenia which persisted in spite of clinical and laboratory improvement. This presentation is done because of the low prevalence or infrequent diagnosis of anicteric hepatitis due to cytomegalovirus in normal individuals. Most of the literature refers to congenital cases, premature babies, or patients with debilitating or immunocompromising diseases.